Uji Efektivitas Ekstrak Daun Binahong (Anredera cordifolia (TEN) Steenis) terhadap Jumlah Fibroblas dan Ketebalan Kolagen pada Luka Infeksi Tikus Wistar - Ratu, Maria T H; Syahrial, Iwan; Hermanu, Liliek (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Binahong (Anredera cordifolia) is a medicinal plant that can be used to accelerate the healing process of wound infections. The purpose of this study was to determine the effect of the ethanol extract of binahong leaves (Anredera cordifolia) on the healing process of incision wounds infected by Staphylococcus aureus. The ethanol extract of binahong leaves is made in the form of ointments to facilitate the application and release of the drug into the skin layer. The study used 24 male Wistar rats which were divided into 4 treatment groups namely the group without treatment, the group with fusidic acid ointment, the group with 20% extract of binahong leaf ethanol extract and the group with 40% extract of binahong leaf ethanol. Infected mice were treated and then observed the number of fibroblasts and collagen thickness on day 3 and day 7. Data was analyzed using One Way Anova followed by Duncan Test. The results showed that the ethanol extract of binahong leaves 40% could increase the number of fibroblasts on the 3rd day (43.33 ± 8.08) and the 7th day (61.67 ± 7.02), the ethanol extract of the binahong leaf 20% on 3rd day (31.67 ± 5.50) and 7th day (57.00 ± 7.55). The ethanol extract of binahong leaves 40% increased the thickness of collagen on the 3rd day (10.37 ± 2.69) and the 7th day (16.55 ± 0.32), the ethanol extract of the binahong leaf 20% on the 3rd day ( 8.87 ± 0.71) and 7th day (12.09 ± 1.26). Based on the results of the study, it can be concluded that the ethanol extract of binahong leaves 40% can accelerate the healing process of wound infections by increasing the number of fibroblasts and collagen thickness better than the administration of ethanol extracts of binahong leaves 20%.